2016
DOI: 10.1093/pcp/pcw171
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Tobacco Lines Expressing Sense or AntisenseFERROCHELATASE 1RNA Show Modified Ferrochelatase Activity in Roots and Provide Experimental Evidence for Dual Localization of Ferrochelatase 1

Abstract: In plants, two genes encode ferrochelatase (FC), which catalyzes iron chelation into protoporphyrin IX at the final step of heme biosynthesis. FERROCHELATASE1 (FC1) is continuously, but weakly expressed in roots and leaves, while FC2 is dominantly active in leaves. As a continuation of previous studies on the physiological consequences of FC2 inactivation in tobacco, we aimed to assign FC1 function in plant organs. While reduced FC2 expression leads to protoporphyrin IX accumulation in leaves, FC1 down-regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 48 publications
2
18
0
Order By: Relevance
“…We are aware that recent reports have cast doubt on the translocation of FC into Arabidopsis mitochondria (Lister, Chew, Rudhe, Lee, & Whelan, ; Woodson et al, ). Nevertheless, we recently demonstrated FC activity in the mitochondria of tobacco plants, supported by immunological evidence for FC (Hey et al, ). In parallel, studies on the recently characterized ATHEMN1 ‐encoded coproporphyrinogen oxidase have shown that this protein is translocated into mitochondria (Pratibha et al, ).…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…We are aware that recent reports have cast doubt on the translocation of FC into Arabidopsis mitochondria (Lister, Chew, Rudhe, Lee, & Whelan, ; Woodson et al, ). Nevertheless, we recently demonstrated FC activity in the mitochondria of tobacco plants, supported by immunological evidence for FC (Hey et al, ). In parallel, studies on the recently characterized ATHEMN1 ‐encoded coproporphyrinogen oxidase have shown that this protein is translocated into mitochondria (Pratibha et al, ).…”
Section: Discussionsupporting
confidence: 59%
“…In the present work, comparison of FC1 and FC2 mRNA levels in wild-type embryos suggests that FC1 is the predominant FC isoform during embryo maturation. The successful complementation of the (Hey et al, 2016). In parallel, studies on the recently characterized ATHEMN1encoded coproporphyrinogen oxidase have shown that this protein is translocated into mitochondria (Pratibha et al, 2017).…”
Section: In Arabidopsis Fc2 Can Fully Substitute Fc1 Function Undementioning
confidence: 97%
See 2 more Smart Citations
“…In plants, the heme synthesis pathway is located in the plastids (Tanaka and Tanaka, ), but its last step, i.e. the chelation of iron, was proposed to be also performed in mitochondria (Chow et al ., , ; Hey et al ., ), however this has been disputed (Lister et al ., ; Masuda et al ., ; Woodson et al ., ). Several proteins involved in heme biosynthesis were identified in our analysis (Dataset S3, worksheet #8), albeit at low copy numbers (<80 copies), indicating etioplast contamination of our mitochondria isolations.…”
Section: Resultsmentioning
confidence: 99%